2010
DOI: 10.4018/jmdem.2010040104
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Image Classification Using Multi-Fractal Spectra

Abstract: Tissue image classification is a challenging problem due to the fact that the images contain highly irregular shapes in complex spatial arrangement. The multi-fractal formalism has been found useful in characterizing the intensity distribution present in such images, as it can effectively resolve local densities and also represent various structures present in the image. This paper presents a detailed study of feature vectors derived from the distribution of Holder exponents and the geometrical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…2.1 Applying multifractal analysis in research of cancer Many researches have shown existing correlation between fractal and multifractal parameters and the tumours, or pathology forms (Baish et al 1998;Budimlija 2001;Buldyrev et al 1994;Bulmore et al 1994;Bunde et al 1990Bunde et al , 1991Byng et al 1996;Fenoglio-Preiser et al 1989;Claridge et al 1992;Coffey 1998;Cross 1994Cross , 1997Reljin et al 2000Reljin et al , 2002Reljin et al , 2008Reljin et al , 2009Stojic et al 2006;Ballerini et al 2003;Roy et al 2011;Mukundan and Hemsley 2010). It has been shown that tissue images contain several fractal structures with varying dimension at varying strengths (Reljin et al 2000(Reljin et al , 2002Mukundan and Hemsley 2010).…”
Section: Multifractal Analysis In Image Processingmentioning
confidence: 96%
See 2 more Smart Citations
“…2.1 Applying multifractal analysis in research of cancer Many researches have shown existing correlation between fractal and multifractal parameters and the tumours, or pathology forms (Baish et al 1998;Budimlija 2001;Buldyrev et al 1994;Bulmore et al 1994;Bunde et al 1990Bunde et al , 1991Byng et al 1996;Fenoglio-Preiser et al 1989;Claridge et al 1992;Coffey 1998;Cross 1994Cross , 1997Reljin et al 2000Reljin et al , 2002Reljin et al , 2008Reljin et al , 2009Stojic et al 2006;Ballerini et al 2003;Roy et al 2011;Mukundan and Hemsley 2010). It has been shown that tissue images contain several fractal structures with varying dimension at varying strengths (Reljin et al 2000(Reljin et al , 2002Mukundan and Hemsley 2010).…”
Section: Multifractal Analysis In Image Processingmentioning
confidence: 96%
“…It has been shown that tissue images contain several fractal structures with varying dimension at varying strengths (Reljin et al 2000(Reljin et al , 2002Mukundan and Hemsley 2010). MF analysis can be applied to gray-level images, in general.…”
Section: Multifractal Analysis In Image Processingmentioning
confidence: 98%
See 1 more Smart Citation
“…the local dimension) is known as the “Holder exponent” or α values [ 101 , 102 ]. In image data analysis, α values reflect the local behavior of the intensity measure that are of 4 different types [ 105 , 106 ]. The corresponding image is often referred to as the α –image.…”
Section: Computational Modelingmentioning
confidence: 99%